Jahresbericht des Vereins Kunsthalle Bern 1990 / 91. - Hahnloser, Bernhard; Kunsthalle Bern (Bern : Kunsthalle Bern, 1991)
Hoever, Lisa ; Leuenberger, Otto ; Pedretti, Gian ; Welling, James ; Alexander, Vikky ; Huws, Bethan ; Milroy, Lisa ; Gober, Robert ; Dorner, Helmut ; etc.
Duits
boek